Dielectric and transport properties of Zn-substituted cobalt ferrites (Journal of Bangladesh Academy of Sciences, 2013)
Effect of Zn content on the dielectric and transport properties of CoZnxFe2-xO4 (x = 0.0, 0.1, 0.2, 0.3 and 0.4), prepared by standard double sintering ceramic technique, sintered at 1000°C for 4 hours were investigated. The X-ray diffraction (XRD) pattern of the prepared samples showed single phase inverse-spinel structure without any detectable impurity. Lattice constant of the samples increased with the increasing Zn concentration which follows Vegards law. The theoretical densities of these samples remained almost constant whereas the bulk density decreased with Zn content up to x = 0.2. But with further increase of Zn content the bulk density increased. The porosity of the prepared samples showed the opposite trend. The dielectric constant (??) measurement showed the normal dielectric behavior of the prepared ferrite. The DC electrical resistivity of the prepared samples decrease with increasing temperature which indicates the semiconducting behavior of the prepared ferrites. The Zn concentration showed pronounced effect on the resistivity at room temperature. Possible explanation for the observed features of densities, porosity, dielectric constant and resistivity of the studied samples are discussed. DOI: http://dx.doi.org/10.3329/jbas.v37i1.15683 Journal of Bangladesh Academy of Sciences, Vol. 37, No. 1, 73-82, 2013